INDONESIAN ICT-BASED TEACHING OF ENGLISH-SPEAKING SKILL: A QUALITATIVE SYSTEMATIC REVIEW - Effendy, Muhammad Burhanuddin; Taufik, Moh. (Universitas Muhammadiyah Metro, 2023)
The fact that technology is inevitable nowadays in education has shifted the traditional teaching method to modern. It offers teachers various accessible facilities to support English learning based on context and needs. This paper is objected to eliciting how the teaching of English-speaking skills is integrated with Information and Communication Technology in the Indonesian context. It employs a qualitative systematic review method that synthesizes the existing studies related to the topic involving its' procedures and how those procedures bring success to learners. It has six main steps; (1) topic formulation, (2) overall study design, (3) sampling, (4) data collection, (5) data analysis, and (6) data presentation. The findings provide some insights for education developers to design methods and activities for speaking. Moreover, future researchers are suggested to explore rarely discussed areas, including young learners and unpopular technologies related to English teaching. It is also found that Information and Communication Technology based teaching speaking in Indonesia has significantly developed through the years, especially as a learning material using video, movies, and podcasts.